Historicizing Ethno-Religious and Political Conflicts in West Africa: The Malian Case - Dione, Saliou; Togola, Bakaye (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
This article historicizes ethno-religious and political conflicts in West Africa with Mali as a case in point. It looks at how foreign and donors' conditioned aid can pose a threat to peaceful existence and survival of West African States. In fact, Mali has since its independence been beset by an extraordinary heavy burden of conflicts. It is either suffering from rebellions or political instability. Added to this, are the current religous problems which are undermining its territorial unity as a result of rising questions and distrust between northern and southern communities. This paper analyzes the reasons for the central authorities' opposition to the northern population, namely the Tuareg and Arabs, on the one hand, and the States to the military, on the other hand. It also brings to light the politically, religiously, and militarily 'divisive' roles of external stakeholder such as the naighboring and Gulf countries, France and the international community as it examines the couses and impacts of the political, social, and religious fragmentations, using a historical perspective, and provides for endogenous and exogenous solutions.